Pesan moral dalam film Mencuri Raden Saleh karya Angga Dwimas Sasongko - Ayu Aprilliani; Alfitriana Purba (Jurnal Komunitas Bahasa, 2023)
This journal examines a moral message contained in the film Stealing Radenl Saleh Karyal Angga Dwimasl Sasongko. The main problem in this research is How the Moral Message contained in the film Stealing Raden Saleh will have benefits for those who want to watch this film. The purpose of this research is to describe the moral message contained in the film Mencuri Raden Saleh so that viewers can draw positive conclusions for those who want to watch it. In this research, qualitative research methods were used. The data source for line research is the film Stealing Raden Salehl by Angga Dwimas lSasongko. Collection of data in line research using observation method. The data analysis technique in this study was in the form of selecting several scenes and recording dialogues which were then analyzed according to the main issues in this study. The results of the analysis show that the film Stealing Raden Saleh by Angga Dwimas Sasongko contains two types of moral messages, namely personal and community moral messages.